2016
DOI: 10.1161/jaha.115.002796
|View full text |Cite
|
Sign up to set email alerts
|

Durable Benefits of Cellular Postconditioning: Long‐Term Effects of Allogeneic Cardiosphere‐Derived Cells Infused After Reperfusion in Pigs with Acute Myocardial Infarction

Abstract: BackgroundInfusion of allogeneic cardiosphere‐derived cells (allo‐CDCs) postreperfusion elicits cardioprotective cellular postconditioning in pigs with acute myocardial infarction. However, the long‐term effects of allo‐CDCs have not been assessed. We performed a placebo‐controlled pivotal study for long‐term evaluation, as well as shorter‐term mechanistic studies.Methods and ResultsMinipigs underwent 1.5‐hour mid‐left anterior descending balloon occlusion followed by reperfusion and were randomized to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 47 publications
0
36
0
5
Order By: Relevance
“…12 , and are readily taken up by numerous cell types including macrophages 13 , fibroblasts 14 , and endothelial cells 15 . Here, we extend our recent work on cellular postconditioning by CDCs 1618 by identifying CDC exosomes (CDC exo ) 19 as key elements of the cellular secretome which confer cardioprotection in MI. We further demonstrate that miR-181b within CDC exo is a critical mediator of macrophage polarization in vitro and cardioprotection in vivo .…”
Section: Introductionmentioning
confidence: 58%
“…12 , and are readily taken up by numerous cell types including macrophages 13 , fibroblasts 14 , and endothelial cells 15 . Here, we extend our recent work on cellular postconditioning by CDCs 1618 by identifying CDC exosomes (CDC exo ) 19 as key elements of the cellular secretome which confer cardioprotection in MI. We further demonstrate that miR-181b within CDC exo is a critical mediator of macrophage polarization in vitro and cardioprotection in vivo .…”
Section: Introductionmentioning
confidence: 58%
“…It its interesting to note that LV structure and function were preserved in CDC-treated spontaneously hypertensive rats at 28 days post-AMI in comparison with rats that had received phosphate-buffered saline (Figure 2), verifying that the effects are durable (as the Marbán laboratory had shown in another pig study). 90 …”
Section: Cellular Postconditioningmentioning
confidence: 99%
“…When allogeneic cells were administered immediately after reperfusion in porcine infarct models, favorable remote zone remodeling was seen after mesenchymal precursor cells (MPCs) 6 and CBSCs 4 from the present study. Directionally similar results in myocyte area were found after allogeneic CDCs administered after reperfusion although myocyte nuclear density was not reported 9 . In contrast, several studies utilizing regional cell administration several weeks after MI have demonstrated reductions in infarct size but failed to show major effects on remote zone myocyte hypertrophy 1012 .…”
mentioning
confidence: 56%
“…Thus, it seems plausible that the mechanism of action of CBSCs may actually reflect acute modulation of the host inflammatory response to myocardial injury in the ischemic as well as remote region of the heart. Further studies will be required to investigate this but similar immune modulatory actions have already been identified for CDCs 9 and MSCs 13 . The second relates to the time course of the functional improvement in CBSC-treated animals.…”
mentioning
confidence: 66%